(untitled) (Світ фінансів, 2017)
Кізима Т. О. Суспільний добробут та прагматика його оцінки в Україні. Розглянуто історичні аспекти розвитку вчення про суспільний добробут та вплив представників окремих наукових шкіл на його формування. Охарактеризовано моделі суспільного добробуту. Здійснено аналіз основних показників, які використовуються для оцінки суспільного добробуту в Україні. Запропоновано окремі заходи щодо підвищення якості життя населення та досягнення належного рівня добробуту суспільства в цілому. Kizyma T. Social prosperity and the pragmatics of its evaluation in Ukraine. The historical aspects of development of study about public welfare and influencing of representatives of separate scientific schools on his forming are considered. The models of public welfare are described. The basic indexes which are used for estimation of public welfare in Ukraine is analysis. Separate measures on upgrading life of population and achievement of the proper level of welfare of society are offered.